Persepsi Mahasiswa Terhadap Penggunaan Chat GPT dalam Pembelajaran di Perguruan Tinggi - Fithra Ramadian; Rahman, Rahman (Edunomics Journal, 2025)
This study aims to explore students' perceptions of the use of Chat GPT in higher education learning. The rapid development of artificial intelligence (AI) technology has significantly influenced various aspects of education, including the adoption of AI-powered tools such as Chat GPT. This research employs a qualitative approach using case studies to examine how students in the Economics Education program at Universitas Tanjungpura perceive and utilize Chat GPT in their learning process. Data were collected from 100 students through questionnaires and in-depth interviews. The findings reveal that the majority of students have a positive perception of Chat GPT, citing its ability to facilitate understanding of complex materials, improve learning efficiency, and enhance motivation. However, some concerns were also identified, including over-reliance on technology, accuracy of information, and the need for proper guidance in its usage. The study suggests that while Chat GPT can be an effective learning aid, it should be integrated with appropriate pedagogical strategies to maximize its benefits. These findings provide insights for educators and institutions in optimizing AI-based technology for higher education learning